(3EHOGY MceI GdMcje aj HjGf HSe Gddg GdQMef GdQMjes - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdHSedI JTQjYI HGdGaJJGM GdQMef GdPj LYdgG dhUhd cd HQcI gh GdeaJGM GdQMje GdPj LYdgG dbGUO cd NjQ GdfLGMs
(3BNQgG (B:s
(3CjVG dcf ef fbU GdMQcI hRjGOI GdMQa EdG Gfge de jcJHhG GdCda YfO GSJYeGdg eY GddGe hCeG YfO GdEVGaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 68s
(3eYLe GdeDdajf (B3 / 692s
(3YKeGfdj eDdadQj (B1 / 296s
(3GdCRgQjI (B3 / 755s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds